Loess-loaded silica gel material as well as preparation method and application thereof

By loading silicone gel on the surface of loess particles, loess-loaded silicone gel material is prepared, which solves the problems of low permeability of loess and insufficient water purification capacity, effectively adsorbing nitrogen and phosphorus in runoff, and improves the rainwater treatment facilities. Purification ability.

CN119430843APending Publication Date: 2025-02-14XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411724029.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The low permeability of loess in traditional fillers limits its application in rainwater treatment facilities, resulting in insufficient water purification capacity and inability to effectively remove nitrogen and phosphorus from runoff, which leads to eutrophication of urban water environment.

Method used

Loess-loaded silicon gel material is prepared by loading silicone gel on the surface of loess particles, and water glass and silicon phosphate are used as modifiers to improve the permeability of loess and the adsorption capacity of pollutants.

Benefits of technology

The permeability of loess has been improved, and it can effectively adsorb nitrogen and phosphorus in runoff, improve the water quality purification capacity of rainwater treatment facilities, and reduce the risk of eutrophication in urban water environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a loess-loaded silica gel material, a preparation method and application thereof, the loess-loaded silica gel material comprises the following raw materials: loess particles, water glass and silicon phosphate, the mass ratio of the loess particles to the water glass is (90-94): (6-10); the mass ratio of the silicon phosphate to the sum of the loess particles and the water glass is (2-2.5): (97.5-98); the preparation method comprises the following steps: sieving loess with a 12-16-mesh sieve to obtain loess particles with the particle size of less than 2mm; the preparation method comprises the following steps: uniformly mixing loess particles and water glass according to a mass ratio of (90-94): (6-10) to obtain a mixture A; silicon phosphate and the mixture A are mixed according to the mass ratio of (2-2.5): (97.5-98), continuous stirring is conducted for 5-8 min, and a mixture B is obtained; curing the mixture B for 14-21 days, and then naturally air-drying to obtain the loess-loaded silica gel material. The obtained loess-loaded silica gel material can be applied to filler of rainwater treatment facilities; the prepared loess-loaded silica gel material is good in permeability and has a good adsorption effect on nitrogen and phosphorus in runoff.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of loess-loaded silica gel, and in particular relates to a loess-loaded silica gel material, a preparation method and application thereof. Background Art

[0002] The continuous expansion of impermeable ground has a great negative impact on the water cycle. In cities, the frequency of floods is gradually increasing. These man-made factors have led to more natural disasters for humans. In order to restore the water cycle in urban areas, many rainwater treatment facilities have been proposed. For example, rain gardens, permeable pavement, green roofs and bioretention facilities.

[0003] Rainwater treatment facilities mainly rely on plants, fillers and microorganisms to purify runoff. Fillers are an important component, and traditional fillers are mainly composed of sand and clay. The water purification capacity of this filler composition is limited. Runoff that has not been thoroughly purified will still cause varying degrees of pollution when entering the water environment. In order to further improve the water purification capacity of rainwater treatment facilities, scholars have proposed many improvement measures. Adding other modifiers to the filler has been proven to effectively improve the pollutant removal capacity of rainwater treatment facilities. However, these modification methods are all based on sandy loam. Making full use of local materials and reducing sand and gravel mining during the construction of rainwater facilities is an effective means to reduce the construction cost of urban rainwater collection systems. When building rainwater collection facilities in loess areas, using loess as filler can greatly reduce construction costs. The low permeability of loess makes it impossible to directly use it as filler for rainwater treatment facilities. Low permeability is a shortcoming that must be overcome for loess to become a filler.

[0004] Silica gel has outstanding specific surface area, pore size, thermal insulation and other characteristics, and is widely used in bonding, fire prevention and other aspects. Silica xerogel can not only be used as a binder, but also can remove metal ions, drugs, and dyes in the water environment. At present, silica xerogel is mainly made by the sol-gel method, and organic silanes, water glass, fly ash, etc. are usually selected as silica precursors. Water glass is an environmentally friendly and inexpensive silicate solution, which is widely used as a hydrophobic agent, curing agent, adhesive, alkali activator, etc. Based on the existing research progress, the experiment proposes to use water glass to modify loess to manufacture loess-loaded silica gel materials.

[0005] The patent application with publication number CN114074986A discloses a bioretention pond filler, which is composed of garden soil, wood chips, volcanic rocks, biochar and sandy loam. The volume ratio of garden soil, wood chips, volcanic rocks, biochar and sandy loam is (25-40): (0-15): (0-10): (0-20): (0-15), the amount of yellow sand, biochar and sandy loam is not zero, and the filler height is 400-800mm. The use of this filler ratio can intercept insoluble phosphorus in rainwater, promote the growth of hydrolytic bacteria, accelerate the hydrolysis reaction process of insoluble phosphorus, adsorb soluble phosphorus, and achieve rapid and thorough removal of phosphorus through the process of interception-hydrolysis-adsorption; however, this filler belongs to physical improvement, not chemical improvement. Secondly, the proportion of volcanic rock and biochar in the filler is relatively large, which greatly increases the construction cost of rainwater treatment facilities. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a loess-loaded silica gel material, a preparation method and an application thereof. By loading silica gel on the surface of loess particles to obtain a low-cost filler, the loess-loaded silica gel material is used as a filler for rainwater treatment facilities, which can effectively control the hydrological parameters of urban runoff and remove nitrogen and phosphorus in the runoff to prevent eutrophication of the urban water environment. The preparation method is simple in process, and the prepared material has high stability, good permeability and good adsorption effect on nitrogen and phosphorus in the runoff.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, wherein the mass ratio of the loess particles to the water glass is (90-94):(6-10); the mass ratio of the silicon phosphate to the sum of the loess particles and the water glass is (2-2.5):(97.5-98).

[0009] The particle size of the loess is less than 2 mm.

[0010] The water glass is a sodium silicate solution with a molar ratio of 3.25-3.35.

[0011] The mass ratio of the loess to water glass is 90:10; the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2:98.

[0012] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0013] Step 1: Pass the loess through a 12-16 mesh sieve to obtain loess particles with a particle size of less than 2 mm;

[0014] Step 2: The loess particles obtained in step 1 and water glass are mixed uniformly in a mass ratio of (90-94): (6-10) to obtain a mixture A; silicon phosphate and the mixture A are mixed in a mass ratio of (2-2.5): (97.5-98), and stirred continuously for 5-8 minutes to obtain a mixture B;

[0015] Step 3: Curing the mixture B obtained in step 2 for 14-21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0016] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention loads silica gel on the surface of loess particles, and the obtained modified filler has good adsorption performance for nutrients (nitrogen and phosphorus). When used as a filler for rainwater treatment facilities, it has the ability to remove nutrients in runoff. The present invention solves the problem of low permeability of loess.

[0019] 2. The materials used in the present invention are cheap and environmentally friendly. The in-situ filler is prepared by using loess, and the filler can be obtained locally in the loess area.

[0020] 3. The present invention selects water glass as a modifier, and the preparation process does not require sintering, which not only makes the production process require sufficiently small energy consumption, but also ensures a simple and easy-to-operate process.

[0021] 4. After a large number of experiments, the ratio of loess particles, water glass and silicon phosphate in the present invention is selected. The mass ratio of loess particles and water glass is (90-94): (6-10) and mixed evenly to obtain mixture A, and the mass ratio of mixture A and silicon phosphate is (97.5-98): (2-2.5) and mixed evenly to obtain mixture B; the mixture B is cured for 14-21 days and then naturally air-dried to obtain a loess-loaded silica gel material; the results show that the prepared loess-loaded silica gel material can meet the permeability requirements of rainwater treatment facilities, and can also effectively adsorb pollutants in runoff and has the ability to purify runoff.

[0022] In summary, the present invention reduces the construction cost of rainwater treatment facilities by loading silica gel on the surface of loess to obtain a modified material that can be used as a filler. In the loess region, a method for in-situ improvement of loess has been determined, which makes the source of filler convenient and low-cost. At the same time, the improved loess also has outstanding water reduction capacity and pollutant adsorption capacity, so that it can effectively control runoff. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with examples. The described examples and their results are only used for the present invention, and should not and will not limit the present invention described in the claims.

[0024] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, wherein the mass ratio of the loess particles to the water glass is (90-94):(6-10); the mass ratio of the silicon phosphate to the sum of the loess particles and the water glass is (2-2.5):(97.5-98).

[0025] The particle size of the loess is less than 2 mm.

[0026] The water glass is a sodium silicate solution with a molar ratio of 3.25-3.35.

[0027] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0028] Step 1: Pass the loess through a 12-16 mesh sieve to obtain loess particles with a particle size of less than 2 mm;

[0029] Step 2: The loess particles obtained in step 1 and water glass are mixed uniformly in a mass ratio of (90-94): (6-10) to obtain a mixture A; silicon phosphate and the mixture A are mixed in a mass ratio of (2-2.5): (97.5-98), and stirred continuously for 5-8 minutes to obtain a mixture B;

[0030] Step 3: Curing the mixture B obtained in step 2 for 14-21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0031] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0032] Example 1

[0033] Loess: Sampling from Bailuyuan, Xi'an.

[0034] Water glass: sodium silicate solution with a molar ratio of 3.25.

[0035] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, the mass ratio of the loess particles to sodium silicate solution is 90:10, and the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2:98.

[0036] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0037] Step 1: crush the loess through a 12-mesh sieve until the particle size is less than 2 mm to obtain loess particles;

[0038] Step 2: Take 90g of loess particles and 10g of sodium silicate solution, mix them evenly to obtain mixture A; mix silicon phosphate and mixture A at a mass ratio of 2:98, and stir continuously for 5 minutes to obtain mixture B;

[0039] Step 3: Curing the mixture B obtained in step 2 for 21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0040] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0041] Example 2

[0042] Loess: Sampling from Bailuyuan, Xi'an.

[0043] Water glass: sodium silicate solution with a molar ratio of 3.35.

[0044] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, the mass ratio of the loess particles to sodium silicate solution is 94:6, and the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2:98.

[0045] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0046] Step 1: crush the loess through a 14-mesh sieve until the particle size is less than 2 mm to obtain loess particles;

[0047] Step 2: Take 94g of loess particles and 6g of sodium silicate solution, mix them evenly to obtain mixture A; mix silicon phosphate and mixture A at a mass ratio of 2:98, and stir continuously for 8 minutes to obtain mixture B;

[0048] Step 3: Curing the mixture B obtained in step 2 for 14 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0049] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0050] Example 3

[0051] Loess: Sampling from Bailuyuan, Xi'an.

[0052] Water glass: sodium silicate solution with a molar ratio of 3.30.

[0053] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, the mass ratio of the loess particles to sodium silicate solution is 90:10, and the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2.5:97.5.

[0054] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0055] Step 1: crush the loess through a 16-mesh sieve until the particle size is less than 2 mm to obtain loess particles;

[0056] Step 2: Take 90g of loess particles and 10g of sodium silicate solution, mix them evenly to obtain mixture A; mix silicon phosphate and mixture A at a mass ratio of 2.5:97.5, and stir continuously for 7 minutes to obtain mixture B;

[0057] Step 3: Curing the mixture B obtained in step 2 for 14 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0058] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0059] Example 4

[0060] Loess: Sampling from Bailuyuan, Xi'an.

[0061] Water glass: sodium silicate solution with a molar ratio of 3.30.

[0062] A loess-loaded silica gel material, whose raw materials include loess particles, water glass and silicon phosphate, the mass ratio of the loess particles to sodium silicate solution is 92:8, and the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2.3:97.7.

[0063] A method for preparing a loess-loaded silica gel material comprises the following steps:

[0064] Step 1: crush the loess through a 15-mesh sieve to a particle size of less than 2 mm to obtain loess particles;

[0065] Step 2: Take 92g of loess particles and 8g of sodium silicate solution, mix them evenly to obtain mixture A; mix silicon phosphate and mixture A in a mass ratio of 2.3:97.7, and stir continuously for 5 minutes to obtain mixture B;

[0066] Step 3: Curing the mixture B obtained in step 2 for 21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

[0067] An application of loess-loaded silica gel material, wherein the prepared loess-loaded silica gel material is used as filler for rainwater treatment facilities.

[0068] The permeability experiment was carried out using the loess-loaded silica gel material obtained in Examples 1-4.

[0069] (1) Penetration test plan

[0070] Rainwater treatment facilities not only have the ability to purify rainwater runoff, but also need to effectively reduce runoff and peak flow. This requires rainwater treatment facilities to have appropriate permeability. Permeability coefficient is the main parameter for evaluating the permeability of fillers. The test adopts the constant head permeability coefficient test method.

[0071] (2) Penetration test results and analysis

[0072] The permeability coefficient of the loess loaded silica gel material prepared by the present invention is 188.41-240.39 mm / h. The permeability coefficient of loess is 0.002 mm / h, and the permeability coefficient of the modified loess loaded with silica gel is significantly increased. This makes the loess loaded silica gel material meet the filler requirements of rainwater treatment facilities.

[0073] The loess-loaded silica gel material obtained in Examples 1-4 was used to carry out nitrogen and phosphorus adsorption tests.

[0074] (1) Nitrogen and phosphorus adsorption test plan

[0075] Take 1g of loess loaded silica gel material and put it into a 50ml conical flask, add 4mg / L, 8mg / L, 20mg / L, 40mg / L, 60mg / L, 80mg / L and 160mg / L of ammonia nitrogen solution (phosphate solution) respectively, and shake at 150r / min, 25℃. After 24h, take out the water sample and filter it through a 0.45μm filter membrane, then measure it at 420nm (700nm) to calculate the ammonia nitrogen (phosphate) adsorption of the material.

[0076] (2) Nitrogen and phosphorus adsorption test results and analysis

[0077] The ammonia nitrogen and phosphate adsorption processes of the loess-loaded silica gel prepared by the present invention are mainly monolayer adsorption, and the maximum adsorption capacities thereof can reach 3.122 and 4.43 mg / g, respectively. The ammonia nitrogen adsorption of the loess-loaded silica gel material is easy to occur, while the phosphate adsorption is not easy to occur.

[0078] The water reduction test was carried out using the loess-loaded silica gel material obtained in Examples 1-4.

[0079] (1) Water reduction test plan

[0080] Loess-loaded silica gel material was added to the biological tributary facility and a simulated rainfall test was conducted. The test was conducted for seven months of simulated rainfall tests, and the facility was subjected to simulated rainfall tests after 2, 4, and 8 days of drought. The water discharge time, water discharge flow rate, water retention, and evaporation of the facility were collected in all rainfall events.

[0081] (2) Water reduction test results and analysis

[0082] The rainwater treatment facility constructed by the present invention using loess-loaded silica gel material will basically not overflow. It also has an outstanding ability to reduce surface runoff. The outflow time in a rainfall event is always late. This is because the outstanding water absorption of the loess-loaded silica gel material causes the runoff in the early stage of the rainfall event to be first absorbed by the filler, and when the filler is saturated with water, the runoff passes through the filler and is discharged. Water retention and transpiration are important hydrological parameters of rainwater treatment facilities. The facility has a good water retention capacity (26%) and a low transpiration (64.42%). The presence of silica gel not only makes it have a large water retention capacity during rainfall, but also a low transpiration during drought.

[0083] The loess-loaded silica gel material obtained in Examples 1-4 was used to conduct a water purification test.

[0084] (1) Water purification test plan

[0085] A rainwater treatment facility with loess-loaded silica gel material as filler was constructed. At the initial stage of construction, simulated runoff was input every day to naturally compact the filler and form a stable microbial community. After the performance of the facility was stable, simulated rainfall tests were started, and different drought periods were set for the test. The facility was tested for simulated rainfall after 2, 4, and 8 days of drought, and the effluent from the facility was collected for the determination of pollutant concentrations.

[0086] (2) Water purification test results and analysis

[0087] The ammonia nitrogen removal rate of the facility constructed by the present invention using the loess-loaded silica gel material is always higher than 80%. Good water retention and low transpiration rate are conducive to the life activities of microorganisms in the filler, which makes the facility also have a good total nitrogen removal rate, up to 90%.

Claims

1. A loess-loaded silica gel material, characterized in that: The raw materials include loess particles, water glass and silicon phosphate. The mass ratio of the loess particles to the water glass is (90-94): (6-10); the mass ratio of the silicon phosphate to the sum of the loess particles and the water glass is (2-2.5): (97.5-98).

2. The loess-loaded silica gel material according to claim 1, characterized in that: The particle size of the loess is less than 2 mm.

3. The loess-loaded silica gel material according to claim 1, characterized in that: The water glass is a sodium silicate solution with a molar ratio of 3.25-3.

35.

4. The loess-loaded silica gel material according to claim 1, characterized in that: The mass ratio of the loess to water glass is 90:10; the mass ratio of the silicon phosphate to the sum of the loess particles and water glass is 2:

98.

5. A method for preparing a loess-loaded silica gel material, characterized in that: The following steps are involved: Step 1: Pass the loess through a 12-16 mesh sieve to obtain loess particles with a particle size of less than 2 mm; Step 2: The loess particles obtained in step 1 and water glass are mixed uniformly in a mass ratio of (90-94): (6-10) to obtain a mixture A; silicon phosphate and the mixture A are mixed in a mass ratio of (2-2.5): (97.5-98), and stirred continuously for 5-8 minutes to obtain a mixture B; Step 3: Curing the mixture B obtained in step 2 for 14-21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

6. The method for preparing a loess-loaded silica gel material according to claim 5, characterized in that: The following steps are involved: Step 1: crush the loess through a 12-mesh sieve until the particle size is less than 2 mm to obtain loess particles; Step 2: Take 90g of loess particles and 10g of sodium silicate solution with a molar ratio of 3.25, mix them evenly to obtain a mixture A; mix silicon phosphate and mixture A at a mass ratio of 2:98, and stir continuously for 5 minutes to obtain a mixture B; Step 3: Curing the mixture B obtained in step 2 for 21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

7. The method for preparing a loess-loaded silica gel material according to claim 5, characterized in that: The following steps are involved: Step 1: crush the loess through a 14-mesh sieve until the particle size is less than 2 mm to obtain loess particles; Step 2: Take 94g of loess particles and 6g of sodium silicate solution with a molar ratio of 3.35, mix them evenly to obtain a mixture A; mix silicon phosphate and mixture A at a mass ratio of 2:98, and stir continuously for 8 minutes to obtain a mixture B; Step 3: Curing the mixture B obtained in step 2 for 14 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

8. The method for preparing a loess-loaded silica gel material according to claim 5, characterized in that: The following steps are involved: Step 1: crush the loess through a 16-mesh sieve until the particle size is less than 2 mm to obtain loess particles; Step 2: Take 90g of loess particles and 10g of sodium silicate solution with a molar ratio of 3.30, mix them evenly to obtain mixture A; mix silicon phosphate and mixture A at a mass ratio of 2.5:97.5, and stir continuously for 7 minutes to obtain mixture B; Step 3: Curing the mixture B obtained in step 2 for 14 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

9. The method for preparing a loess-loaded silica gel material according to claim 5, characterized in that: The following steps are involved: Step 1: crush the loess through a 15-mesh sieve to a particle size of less than 2 mm to obtain loess particles; Step 2: Take 92g of loess particles and 8g of sodium silicate solution with a molar ratio of 3.30, mix them evenly to obtain a mixture A; mix silicon phosphate and mixture A at a mass ratio of 2.3:97.7, and stir continuously for 5 minutes to obtain a mixture B; Step 3: Curing the mixture B obtained in step 2 for 21 days, and then air-drying it naturally to obtain a loess-loaded silica gel material.

10. An application of loess-loaded silica gel material, characterized in that: The loess-loaded silica gel material described in any one of claims 1 to 4 or the loess-loaded silica gel material prepared by any one of the methods of claims 5 to 9 is used as filler for rainwater treatment facilities.

Citation Information

Patent Citations

  • Bioretention pond filler

    CN114074986A